2018
DOI: 10.1002/brb3.957
|View full text |Cite
|
Sign up to set email alerts
|

Central cholinergic system mediates working memory deficit induced by anesthesia/surgery in adult mice

Abstract: BackgroundPostoperative cognitive dysfunction (POCD) is consistently associated with increased morbidity and mortality, which has become a major concern of patients and caregivers. Although POCD occurs mainly in aged patients, it happens at any age. Previous studies demonstrated that anesthesia/surgery had no effects on reference memory of adult mice. However, whether it impairs working memory remains unclear. Working memory deficit would result in many deficits of executive function. We hypothesized that anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…We did not investigate how other domains of learning and memory such as working memory changed after multiple anesthesia/surgery. In our previous study, we demonstrated that although the spatial reference memory was not changed after a single anesthesia/surgery, the working memory was impaired in young adult mice [33]. Although exposure to multiple anesthesia/surgery in such a short period is not common in clinical practice, our data from the present study indicated that the effects of multiple anesthesia/surgery on learning and memory are no worse than those of a single anesthesia/surgery.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…We did not investigate how other domains of learning and memory such as working memory changed after multiple anesthesia/surgery. In our previous study, we demonstrated that although the spatial reference memory was not changed after a single anesthesia/surgery, the working memory was impaired in young adult mice [33]. Although exposure to multiple anesthesia/surgery in such a short period is not common in clinical practice, our data from the present study indicated that the effects of multiple anesthesia/surgery on learning and memory are no worse than those of a single anesthesia/surgery.…”
Section: Discussioncontrasting
confidence: 46%
“…The central cholinergic system is essential for learning and memory, including the modulation of the acquisition, encoding, consolidation, reconsolidation, extinction, and retrieval of memory [32]. Our previous work showed that central cholinergic neuronal degeneration facilitates the development of POCD [10,33]. In this study, the central cholinergic system was stable after multiple anesthesia/surgery, corresponding to normal learning and memory.…”
Section: Discussionmentioning
confidence: 48%
“…The use of AChE inhibitors elevates the concentration of acetylcholine in treated tissues, and can have the ability to enhance cognitive performance (Brousseau et al, 2007 ). A recent study has shown that donepezil could reverse cognitive impairments in aged rodents subjected to anesthesia and surgery (Zhang et al, 2018 ). Moreover, there are many clinical trials evaluating the effects of FDA-approved AChE inhibitors, such as rivastigmine and donepezil, on the prevention and treatment of POCD 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al found relatively higher ChAT activity and choline intake in rats during the MWM task [22]. Zhang et al performed anesthesia and surgery on rats and found that memory deficit was associated with defects in the central cholinergic system [23]. Therefore, in this study, the expression of ChAT in the mouse hippocampus was studied to determine whether its expression could reflect the effect of hepatic ischemia-reperfusion injury on cognitive function.…”
Section: Discussionmentioning
confidence: 99%